Safe to be open study on the protection of research data and recommendations for access and usage - Guibault, Lucie; Wiebe, Andreas (Universitätsverlag Göttingen, 2013)
This study addresses the most important legal issues when implementing an open access e-infrastructure for research data. It examines the legal requirements for different kinds of usage of research data in an open access infrastructure, such as OpenAIREplus, which links them to publications. The existing legal framework regarding potentially relevant intellectual property (IP) rights is analysed from the general European perspective as well as from that of selected EU Member States. Various examples and usage scenarios are used to explain the scope of protection of the potentially relevant IP rights. In addition different licence models are analysed in order to identify the licence that is best suited to the aim of open access, especially in the context of the infrastructure of OpenAIREplus. Based on the outcomes of these analyses, some recommendations to the European legislator as well as data- and e-infrastructure providers are given on improving the rights situation in relation to research data.